On the meaning of central bank independence - G. M. Wessels (South African Journal of Economic and Management Sciences, 1998)
This article aims to clarify the meaning of the multifaceted term central bank independence. Such independence cannot be understood in an absolute sense, because the elected government in a democratic society remains the highest authority in respect of economic policy-making too. Nevertheless, central banks globally are currently endowed with strong relative independence. This may be separated into two broad categories, namely formal and informal independence. Political and economic independence are identified as elements of the former, and their various subcategories are expounded below. Informal independence is then highlighted as the more important component of independence, of which personalities, professionalism and public support are crucial. However, an ideal combination of the determinants of independence is hard to find.